Exploring the intricate relationship between foreign language anxiety, attention and self-repairs during L2 speech production. (April 2022) - Zuniga, Michael; Simard, Daphnée
Abstract: The present study investigates relationships between foreign language anxiety (FLA), attentional control and the quality of L2 speech production as observed through self-initiated self-repair behavior (SISR). Participants were 34 French L1 English L2 speakers. We used a measure of FLA (Dewaele & MacIntyre, 2014 ) and a measure of attention shift capacity (Reitan, 1958 ). SISR data were collected through a picture-cued narration task. Statistical analyses revealed that increased FLA was significantly linked to increases in discourse-level SISRs. Anxious speakers appear to have more difficulty finding their words preverbally, as they speak in an L2 than less anxious speakers. A second series of analyses revealed that this link is moderated by L2 speakers' attentional control. Only speakers with low attentional control appear to be impacted by this FLA effect. Results are discussed in light of the broaden-and-build theory of emotions.